Graphene oxide-gallic acid nanodelivery system for cancer therapy - Dorniani, Dena; Saifullah, Bullo; Barahuie, Farahnaz; Arulselvan, Palanisamy; Hussein, Mohd Zobir; Fakurazi, Sharida; Twyman, Lance J. (SpringerOpen, 2016)
Despite the technological advancement in the biomedical science, cancer remains a life-threatening disease. In this study, we designed an anticancer nanodelivery system using graphene oxide (GO) as nanocarrier for an active anticancer agent gallic acid (GA). The successful formation nanocomposite (GOGA) was characterized using XRD, FTIR, HRTEM, Raman, and UV/Vis spectroscopy. The release study shows that the release of GA from the designed anticancer nanocomposite (GOGA) occurs in a sustained manner in phosphate-buffered saline (PBS) solution at pH 7.4. In in vitro biological studies, normal fibroblast (3T3) and liver cancer cells (HepG2) were treated with different concentrations of GO, GOGA, and GA for 72 h. The GOGA nanocomposite showed the inhibitory effect to cancer cell growth without affecting normal cell growth. The results of this research are highly encouraging to go further for in vivo studies.